2009
DOI: 10.1111/j.1600-9657.2009.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of general dentists in the current guidelines for emergency treatment of avulsed teeth and dental trauma prevention

Abstract: A high prevalence of dental trauma exists and its effects on function and esthetics deserve the attention of general dentists. The aim of this study was to assess the level of general dental practitioners' (GDPs) knowledge about guidelines for dental avulsion and its prevention using a questionnaire. The 21-item questionnaire was distributed among 264 GDPs and the survey was realized between August-November 2006. The data obtained were statistically analyzed using descriptive analysis and Pearson's Chi-square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
40
4
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 25 publications
12
40
4
10
Order By: Relevance
“…Some studies have shown a negative association between time elapsed since graduation and knowledge on dental trauma [1,12,18]. The present study, in which 67% of the dentists had more than 10 years of professional experience, showed a negative correlation between time since graduation and performance in the questions on hypothetical clinical cases of avulsed teeth.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Some studies have shown a negative association between time elapsed since graduation and knowledge on dental trauma [1,12,18]. The present study, in which 67% of the dentists had more than 10 years of professional experience, showed a negative correlation between time since graduation and performance in the questions on hypothetical clinical cases of avulsed teeth.…”
Section: Resultssupporting
confidence: 50%
“…The dental avulsion management have been evaluated among dental students [10], dentists [11][12][13], accident and emergency doctors [14] and schoolteachers [15] in several countries. All levels of professional exhibited insufficient knowledge for correct decision making.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Orofacial and dental trauma can result from falls, assaults, motor vehicle accidents and sporting accidents. 11 Injuries consist of simple tooth concussion, fracture, luxation and avulsion, laceration of the gingiva, and jaw fractures.…”
Section: Introductionmentioning
confidence: 99%
“…11 Injuries consist of simple tooth concussion, fracture, luxation and avulsion, laceration of the gingiva, and jaw fractures. [1][2][3]12 Orofacial and dental injuries commonly occur during sports participation, with as many as 31% of orofacial injuries reported to result from trauma while playing sports. 4,[12][13][14] Of 9543 patients treated over 10 years by a maxillofacial surgery department in an Australian hospital, sports injuries (31%) came only second to activities of daily life (38%) as the reason of presentation.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, immediate and proper treatment can minimize the emotional distress experienced by patients and improve case prognosis. 1 However, dentists must be familiar with the different types of injuries involving teeth and supporting tissues, and must know how to handle trauma cases, from emergency care to the most suitable clinical protocol for each type of injury. An ill-advised first treatment may have esthetic and functional implications that will worsen the discomfort and cause greater inconveniences to the patient, possibly even increasing treatment costs if more complex procedures are required.…”
mentioning
confidence: 99%